Strategi Komunikasi Pemasaran Untuk Menciptakan Brand Awareness (Studi Kasus Pada Produk Sabun Organic Dr Bronnerâ€™s) - Parlin Harbet; Jolyanto Jolyanto (Jurnal Public Relations (J-PR), 2023)
The impact of this pandemic has also changed the lifestyle of most people who previously used products containing chemicals, now have started to switch to products labeled natural (natural) or organic. The growth of users of organic products in Indonesia has increased from previous years with an increase reaching thirty percent, and is predicted to continue to increase in the years to come. The method used is a qualitative method with an analytical descriptive, verification and exploratory approach. The type of data collected is primary data obtained from unstructured interviews to information sources. The data analysis technique uses a qualitative descriptive model in the form of data collection, data reduction, data display, and conclusions. In building brand awareness of Dr Bronner's products using a message strategy which is divided into several important pillars in conveying messages in the process of marketing Dr Bronner's soap in Indonesia where the umbrella message (key message) is â€œClean Beauty, Effective & Iconicâ€ this is because it is still many people in Indonesia still choose personal care not based on the benefits of personal care (in this case, soap) and also the ingredients used in the soap they use. Dr. Bronner's in Indonesia has planned a communication strategy by highlighting the advantages or advantages of the product as the main key in marketing the product.